CCR7-mediated T follicular helper cell differentiation is associated with the pathogenesis and immune microenvironment of spinal cord injury-induced immune deficiency syndrome - Li, Chaochen; Wu, Chunshuai; Xu, Guanhua; Liu, Yang; Chen, Jiajia; Zhang, Jinlong; Hong, Hongxiang; Ji, Chunyan; Cui, Zhiming (Frontiers in Neuroscience, 2022)
Spinal cord injury-induced immune deficiency syndrome (SCI-IDS) is a disease characterized by systemic immunosuppression secondary to spinal cord injury (SCI), dramatically increasing the likelihood of infection and being difficult to treat. T follicular helper (Tfh) cells regulated by chemokine receptor CCR7 are associated with SCI-IDS after acute SCI. The present study explored the effects of CCR7 on SCI-IDS occurrence and immune microenvironment composition. Gene expression profile data were collected from the Gene Expression Omnibus (GEO) database of peripheral blood leukocytes from SCI and non-SCI subjects. Based on differential gene analysis, protein-protein interaction (PPI) network, and risk model construction, the expression level of CCR7 was prominently related to acute SCI, and CCR7 was significantly under-expressed after acute SCI. Next, we constructed and deployed a clinical prediction model to identify patients with acute SCI to aid its diagnosis. Using Gene Ontology (GO) and Gene Set Enrichment Analysis (GSEA), we discovered that immune-related biological processes, such as T cell receptor signaling pathway, were suppressed, and chemokine-related signaling pathways were activated after acute SCI. Immune infiltration analysis performed with ssGSEA and CIBERSORT suggested that Tfh cell function was significantly correlated with CCR7 expression levels and reduced considerably after acute SCI. Acute SCI was divided into two subtypes, and we integrated multiple classifiers to analyze and elucidate the immunomodulatory relationships in both subtypes jointly. Our results suggested that CCR7 suppressed the immunodeficiency phenotype by activating the Chemokine Signaling pathway in Tfh cells. Additionally, CCR7 exhibited potential as a diagnostic marker for acute SCI.